Analisis Kegagalan Cylinder Head Studs pada Mesin Diesel Empat Langkah dengan Metode Elemen Hingga - Pradhana Kurniawan; Yusuf Adi Sudrajat (University of Merdeka Malang, 2022)
Stud bolts are widely used in mechanical engineering to join two or more components. Sometimes these components fail due to fatigue, and cracks. Fatigue damage is caused by fluctuations between stress and strain that can change the permanent structure of the material, and can cause cracks or fractures after fluctuating several times. The occurrence of fatigue fractures is caused by the simultaneous action of cyclic stresses, tensile stresses, and plastic strains. Each cylinder head has 6 studs. Four cylinders stud heads were damaged on the top side, adjacent to the start of the second root thread, on the top side of the stud. Stud damage occurs over and over again, even on new cylinder head studs. By analyzing the causes of stud damage, simulations can be carried out with the aim of determining the maximum stress and fatigue life of the cylinder head studs.